Mucosal Prevalence and Interactions with the Epithelium Indicate Commensalism of Sutterella spp. - Hiippala, Kaisa; Kainulainen, Veera; Kalliomäki, Marko; Arkkila, Perttu; Satokari, Reetta (Frontiers in Microbiology, 2016)
Sutterella species have been frequently associated with human diseases, such as autism, Down syndrome and inflammatory bowel disease (IBD), but the impact of these bacteria on health still remains unclear. Especially the interactions of Sutterella spp. with the host are largely unknown, despite of the species being highly prevalent. In this study, we addressed the interaction of three known species of Sutterella with the intestinal epithelium and examined their adhesion properties, the effect on intestinal barrier function and the pro-inflammatory capacity in vitro. We also studied the relative abundance and prevalence of the genus Sutterella and S. wadsworthensis in intestinal biopsies of healthy individuals and patients with celiac disease (CeD) or IBD. Our results show that Sutterella spp. are abundant in the duodenum of healthy adults with a decreasing gradient towards the colon. No difference was detected in the prevalence of Sutterella between the pediatric IBD or CeD patients and the healthy controls. Sutterella parvirubra adhered better than the two other Sutterella spp. to differentiated Caco-2 cells and was capable of decreasing the adherence of S. wadsworthensis, which preferably bound to mucus and human extracellular matrix (ECM) proteins. Furthermore, only S. wadsworthensis induced an interleukin-8 (IL-8) production in enterocytes, which could be due to different lipopolysaccharide (LPS) structures between the species. However, its pro-inflammatory activity was modest as compared to non-pathogenic Escherichia coli. Sutterella spp. had no effect on the enterocyte monolayer integrity in vitro. Our findings indicate that the members of genus Sutterella are widely prevalent commensals with mild pro-inflammatory capacity in the human gastrointestinal tract and do not contribute significantly to the disrupted epithelial homeostasis associated with microbiota dysbiosis and increase of Proteobacteria. The ability of Sutterella spp. to adhere to intestinal epithelial cells (IECs) indicate that they may have an immunomodulatory role.